Viability study on the application of advance blasting method in Malaysian shipbuilding industry - Md. Naiem, Mohd. Azzeri (2004)
The main objective of study is to propose application of advance blasting method in Malaysian shipbuilding industry; therefore it is hypothesis by replacing the current method with advance method would be more technically and economically beneficial. From the preliminary survey to the Malaysian shipbuilding or ship repair industry, the abrasive blasting methods are still being implemented for surface preparation. This technology, although effective in coating removal and establishment of surface profile, is laden with inherent problems, American and European yards began realizing the human and environmental consequences of open air abrasive blasting. To overcome such problem, the advanced method of ultra high pressure water jetting is used. However, this advanced ultra high pressure water jetting method is still not been implemented in Malaysian shipbuilding industry. With this back ground, a viability study was carrying out on the application advance blasting method to the local shipbuilding. The study focused on technical and economical aspects and comparison here made among several advance methods and against the present abrasive blasting method. The result of the study indicated that, a. Technically, automated ultra high pressure water jetting is the best blasting method with the cleaning capability of 90 m2 per hour (12 times faster than abrasive blasting method) and equipped with external recovery system. b. On the economic aspect, the automated ultra high pressure water jetting method is only economically viable if the amount of cleaning job per year is larger (more than 34,750 m2), while for small cleaning job, the present method review the most cost effective.